Cavitation Peening: A Review - Hitoshi Soyama (Metals, 2020)
The most popular surface modification technology used to enhance the mechanical properties of metallic materials is shot peening. Shot peening improves fatigue life and strength by introducing local plastic deformation pits. However, the pits increase surface roughness, which is a disadvantage for fatigue properties. Recently, cavitation peening, in which cavitation bubble collapse impacts are used, has been developed as an advanced surface modification technology. The advantage of cavitation peening is the lesser increase in surface roughness compared with shot peening, as no solid collisions occur in cavitation peening. In conventional cavitation peening, cavitation is generated by injecting a high-speed water jet into water. However, cavitation peening is different from water jet peening, in which water column impacts are used. In the present review, to avoid confusing cavitation peening and water jet peening, fundamentals and mechanisms of cavitation peening are described in comparison to water jet peening, and the effects and applications of cavitation peening are reviewed compared with the other peening methods.